Issues and challenges in contemporary affordable public housing schemes in Malaysia: Developing an alternative model - Bilal, Muhammad; Mydin Meera, Ahamed Kameel; Abdul Razak, Dzuljastri (Emerald Group Publishing Limited, 2019)
This study aims to examine the issues and challenges in contemporary affordable public housing schemes and proposes an alternative affordable public housing model for low and middle households in Malaysia. Semi structured in-depth interviews with four government officials were conducted to understand the framework.The overall findings revealed that the growing plights of unaffordability, poor maintenance and mismanagement have undermined the performance of affordable public housing schemes in Malaysia. It also offer guidelines to government officials and managers of public housing to implement Islamic Public-Private Housing Model (IPHCM)